All-Arthroscopic Ulnar Nerve Release and Subcutaneous Transposition - Chuan Zhang, M.D.; Wang-Yu Lu, M.D.; Jiang-Tao Ma, M.D.; Wen-Sheng Wang, M.D.; Sui-Zhu Huang, M.D. (Arthroscopy Techniques)
Cubital tunnel syndrome is a common compressive neuropathy in the upper limb. When nonoperative management has failed to sufficiently improve the condition, various surgical techniques including in situ decompression and ulnar nerve anterior transposition have been undertaken to decompress the nerve, and these can be performed via open or arthroscopic assisted approaches. With open surgery or arthroscopic surgery, good clinical results have been reported. We describe a technique of all-arthroscopic medial bi-portal ulnar nerve release with an anterolateral portal for transient nerve retraction and transposition. This technique allows for a more complete release and maximum protection of the ulnar nerve while reducing surgical scars, relieving postoperative pain, and shortening the recovery time.